2021
DOI: 10.1111/jdi.13643
|View full text |Cite
|
Sign up to set email alerts
|

Corneal confocal microscopy for the diagnosis of diabetic peripheral neuropathy: A systematic review and meta‐analysis

Abstract: Introduction: Corneal confocal microscopy (CCM) is a rapid non-invasive ophthalmic imaging technique that identifies corneal nerve fiber damage. Small studies suggest that CCM could be used to assess patients with diabetic peripheral neuropathy (DPN). Aim: To undertake a systematic review and meta-analysis assessing the diagnostic utility of CCM for sub-clinical DPN (DPN -) and established DPN (DPN + ). Data sources: Databases (PubMed, Embase, Central, ProQuest) were searched for studies using CCM in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 67 publications
2
22
1
Order By: Relevance
“…However, the nerve density values for those with T1D were significantly lower than for the controls at each time point associated consistently with moderately severe peripheral neuropathy. 27 A similar result was reported in a recent study of 19 patients with T1D followed up for a period 2 years; however, the patients were not compared with a control cohort, so the study lacked a direct aging comparison. 5 Our study has similarities to a previous longitudinal study that observed the progression of SBN density in healthy subjects and in those with T1D.…”
Section: Discussionsupporting
confidence: 67%
“…However, the nerve density values for those with T1D were significantly lower than for the controls at each time point associated consistently with moderately severe peripheral neuropathy. 27 A similar result was reported in a recent study of 19 patients with T1D followed up for a period 2 years; however, the patients were not compared with a control cohort, so the study lacked a direct aging comparison. 5 Our study has similarities to a previous longitudinal study that observed the progression of SBN density in healthy subjects and in those with T1D.…”
Section: Discussionsupporting
confidence: 67%
“…A second limitation is the clinical diagnosis of DSPN. Indeed, we did not use more sophisticated modalities, such as nerve conduction velocity, intraepidermal nerve fibre density via skin biopsy, or corneal confocal microscopy, which may enable earlier diagnosis of subclinical DSPN [ 1 , 2 , 29 ]. Moreover, subjects were included in a tertiary care centre, and so results may not be directly applicable to primary care and/or the general T2DM population.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous alternative methods that have been used to assess DPN such as corneal confocal microscopy and quantification of intraepidermal nerve fibre density; however, these tests are not commonly utilized in clinical practice. 19 , 20 …”
Section: Reviewmentioning
confidence: 99%